Stability at different temperatures of turmeric oleoresin encapsulated in maltodextrin/gelatin matrices by freeze-drying - Malacrida, Cassia Roberta [UNESP]; Ferreira, Sungil; Telis, Vania Regina Nicoletti [UNESP] (American Scientific Publishers, 2013)
Turmeric (Curcuma longa L.), which has been used for long time as a spice, food preservative and coloring agent, is a rich source of beneficial phenolic compounds identified as curcuminoids. These phenolic compounds are known for their antioxidant, anti-inflammatory and antimutagenic properties, among others. On the other hand, they are very susceptible to oxidation, requiring protection against oxygen, light and heat. This protection can be achieved by microencapsulation. In this work, the characteristics and the stability of turmeric oleoresin encapsulated by freeze-drying using mixtures of maltodextrin and gelatin as wall materials were studied. Encapsulated turmeric oleoresin was stored at –20, 25 and 60 °C, in the absence of light, and analyzed over a period of 35 days for curcumin and total phenolic contents and color. Results showed that the samples produced with 26% maltodextrin/0.6% gelatin and 22% maltodextrin/3% gelatin presented good encapsulation efficiencies and solubility. In general, the method of encapsulation employed originated products with satisfactory thermal stability, although the encapsulated materials with a higher proportion of maltodextrin in relation to gelatin had better stabilities, especially at –20 and 25 °C temperatures.
Keywords: curcumin; microencapsulation; phenolics; stability; turmeric oleoresin